Ayurvedic Management of Arsha (Piles) : A Clinical Case Study - Samantaray, Sanghamitra (Journal of Neonatal Surgery, 2025)
Background: Arsha (hemorrhoids or piles) is a commonly encountered anorectal condition described extensively in Ayurvedic classics. It manifests due to the vitiation of Tridoshas, particularly Apana Vata, leading to the development of painful and often bleeding growths in the anal region. In modern medicine, hemorrhoids are frequently managed surgically, especially in advanced stages. However, early-stage hemorrhoids can often be managed conservatively. Ayurveda offers a comprehensive, non-surgical approach that targets both the symptoms and the underlying doshic imbalances. Objective: This case study aims to evaluate the efficacy of classical Ayurvedic treatments in the conservative management of internal bleeding piles (Arsha), highlighting their role in symptom relief, bowel regulation, and prevention of recurrence. Methods: A 38-year-old male presented with Grade II internal hemorrhoids characterized by bleeding per rectum, pain during defecation, constipation, and rectal heaviness. Diagnosis was confirmed through clinical and proctoscopic examination. A combination of internal medications (Triphala Guggulu, Abhayarishta, Arshoghni Vati, and Avipattikara Churna), local therapies (Matra Basti with Jatyadi Taila and sitz bath with Panchavalkala decoction), and dietary/lifestyle modifications were administered over a period of 6 weeks. Symptom severity was assessed using a 0–4 Likert scale before and after treatment. Significant clinical improvement was observed. Bleeding and pain completely resolved within 2 weeks, constipation improved markedly, and the patient achieved normal bowel habits by the end of the treatment. The total symptom score reduced from 11/20 to 1/20, indicating a 90.9% improvement. No recurrence was noted during the follow-up period. This case demonstrates that Ayurvedic management can offer a safe, effective, and non-invasive alternative for early-stage hemorrhoids. Classical formulations and local therapies, when tailored according to doshic dominance, can provide substantial relief and prevent the need for surgical intervention. Further clinical studies on larger populations are warranted to substantiate these findings